Sistem Pendukung Keputusan Pemilihan Aternatif Pengelolaan Limbah kelapa Sawit Pada PT.Austindo Nusantara Jaya Agri Siais Kabupaten Tapanuli Selatan Sumatera Utara Menggunakan Metode Analityc Network Process (ANP) - Rizka Pratiwi; Mesran Mesran; Soeb Aripin; Chandra Frenki Sianturi; Lince Tomoria Sianturi (Bulletin of Computer Science Research, 2021)
Oil palm is the largest commodity in several regions in Indonesia. Especially on the islands of Kalimantan and Sumatra. This requires the construction of a palm oil mill (PKS) to produce waste and a very large volume of solid waste and liquid waste. Several alternative solutions that will be considered to deal with this problem are designing a new location, implementing a new location and repairing / structuring an existing location and treating liquid waste and solid waste into appropriate commodities. In choosing this alternative, many criteria must be considered. Therefore, in the selection of alternative palm oil mill effluent using Analysis Network Process (ANP) in decision making.